(3bWYI aj GYeGd cjejGFjI hWHjYjIs
(3ChdgG (B:s
(3ef Chd GdehLhO eYQaI CdGJ hcja jfHZj Cf Jchf CeG GdbOhQ GdNGeS s
(3BNQgG (B:s
(3jDNP RgQI GdCMeQ hGNQ bI HeKdI MJj jQaYhG JQGg MeQkG Ke NP UaGQ KdGKjf HjVI hebOGQ QWd YSd GdfMd hChbjI hfUa GdYbQH GdYQGbj hJSMbI SMbkG s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3GdYfhGf JbOjQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3eJaQbGJs